A new deep-sea species of the snapping shrimp genus Alpheus Fabricius, 1798 (Decapoda: Caridea: Alpheidae) from Kagoshima Bay, Japan - Komai, Tomoyuki; Ohtomi, Jun (Zootaxa, 2018)
A new species of the snapping shrimp genus Alpheus Fabricius, 1798, A. longipalma, is described and illustrated on the basis of material from Kagoshima Bay, Kyushu, Japan. It is referred to the A. brevirostris (Olivier, 1811) species group, and appears closest to A. macroskeles Alcock & Anderson, 1894, known with certainty from the Bay of Bengal and Andaman Sea, and A. talismani Coutière, 1898 from the eastern Atlantic. The greatly elongate minor cheliped in males, being subequal to or longer than the major cheliped with proportionally shorter dactylus distinguish the new species from A. macroskeles. The less elongate antennular peduncle and better-developed, rounded distal lamella of the antennal scaphocerite differentiate the new species from A. talismani. All specimens of the new species were trawled from depths greater than 200 m.